Evaluation of Normal Changes in Pons Metabolites due to Aging Using Turbo Spectroscopic Imaging - Yang, A.; Xiao, X.h.; Wang, Z.l. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: To date, MRS study of both normal and pathologic brains have focused mainly on the supratentorial regions; few studies have investigated the infratentorial regions. However, the pons, an important structure of the brain, is associated with many neurodegenerative diseases and is often damaged by brain trauma. For MRS study of pontine disease, one must obtain MRS reference data on normal metabolite levels in the pons, including data on how these levels vary with age. The aim of this study was to analyze normal, age-related, metabolic changes in the pons by using turbo spectroscopic imaging. MATERIALS AND METHODS: Seventy-eight healthy subjects with ages ranging from 5 days to 78 years were included in this study. NAA/Cr, Cho/Cr, and Cho/NAA ratios were measured by using turbo spectroscopic imaging. The 78 cases were divided into 4 groups by age: 0–5, 6–20, 21–50, and older than 50 years. The metabolite levels were compared with observed age-related changes among the groups. RESULTS: The normal mean pontine metabolite ratios obtained for the combined age groups were NAA/Cr, 2.44 ± 0.45 (mean); Cho/Cr, 1.93 ± 0.25; and Cho/NAA, 0.83 ± 0.28. Statistically significant differences were found in the NAA/Cr between the 0- to 5- and 6- to 20-year-old groups, and among the 6- to 20-, 21- to 50-, and older than 50-year-old groups. A statistically significant difference was found in Cho/Cr between the 0- to 5- and 6- to 20-year-old subjects; however, no differences were found among the 6- to 20-, 21- to 50-, and older than 50-year-old groups. Statistically significant differences in Cho/NAA were also found among the 4 age groups. The NAA/Cr at birth was low, it rose rapidly at 0–5 years, reaching a peak at approximately 10–20 years, and then gradually decreased. The Cho/Cr decreased rapidly at 0–5 years, then continued to decline, and was stable after 20 years of age. CONCLUSIONS: Turbo spectroscopic imaging is a good method for analyzing normal changes in the pons metabolites during growth, maturation, and aging. TSIturbo spectroscopic imaging